Structured Variational Distributions in VIBES - Bishop, Christopher; Winn, John (Proceedings Artificial Intelligence and Statistics, 2003)
Variational methods are becoming increasingly popular for the approximate solution of complex probabilistic models in machine learning, computer vision, information retrieval and many other fields. Unfortunately, for every new application it is necessary first to derive the specific forms of the variational update equations for the particular probabilistic model being used, and then to implement these equations in application-specific software. Each of these steps is both time consuming and error prone. We have therefore recently developed a general purpose inference engine called VIBES ('Variational Inference for Bayesian Networks') which allows a wide variety of probabilistic models to be implemented and solved variationally without recourse to coding. New models are specified as a directed acyclic graph using an interface analogous to a drawing package, and VIBES then automatically generates and solves the variational equations. The original version of VIBES assumed a fully factorized variational posterior distribution. In this paper we present an extension of VIBES in which the variational posterior distribution corresponds to a sub-graph of the full probabilistic model. Such structured distributions can produce much closer approximations to the true posterior distribution. We illustrate this approach using an example based on Bayesian hidden Markov models.
ISBN 0-9727358-0-1